TPU mobile phone shell capable of improving silk-screen precision and preparation method of TPU mobile phone shell

By combining modified TPU material and functional additives, the problem of blurred patterns and insufficient color during the silk screen printing process of TPU mobile phone cases is solved, which improves the screen printing accuracy and pattern stability, while maintaining the elasticity and durability of the material, simplifying the production process and reducing costs.

CN120329708AActive Publication Date: 2025-07-18DONGGUAN YAFEN PLASTIC PROD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510688095.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-27
Publication Date
2025-07-18
Estimated Expiration
2045-05-27

AI Technical Summary

Technical Problem

During the silk screen printing process, existing TPU mobile phone cases have problems such as blurred pattern edges and insufficient color saturation, especially in the details, it is difficult to meet high-precision needs, and traditional coating treatment affects the elasticity and durability of the material.

Method used

Using a combination of modified TPU materials and functional additives, the surface lipophilicity is improved through end-based isocyanate modification, the ink adhesion is enhanced using fluoroalkyl coupling agent and nanosilica, and self-assembly coatings of polytetrafluoroethylene or polydimethylsiloxane, optimize the surface structure and coating thickness to improve screen printing accuracy.

Benefits of technology

Significantly improves screen printing accuracy and pattern stability, maintains the elasticity and durability of the material, simplifies production processes, reduces costs, and maintains the clarity and wear resistance of the pattern during long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120329708A_ABST
    Figure CN120329708A_ABST
Patent Text Reader

Abstract

The invention relates to the field of mobile equipment accessories, and discloses a TPU mobile phone shell capable of improving screen printing precision and a preparation method thereof.The TPU mobile phone shell is prepared from 85%-95% of modified TPU materials, the tensile strength of the modified TPU materials is larger than or equal to 20 MPa, and the elongation at break of the modified TPU materials is larger than or equal to 500%; the functional auxiliary agent comprises a surfactant and a modified nano material, the surfactant is a fluoroalkyl coupling agent, the nano material is amino-functionalized nano silicon dioxide, and the particle size of the nano material is smaller than 200 nm; 1%-3% of pigment, wherein the diameter of pigment particles is less than 1 [mu] m; and 2%-3% of a self-assembled coating material, the coating material is polytetrafluoroethylene or polydimethylsiloxane, and the thickness of the coating is controlled to be 0.05 mm. Through the combination of the modified TPU material and the functional auxiliary agent, the effect of remarkably improving the silk-screen precision and the pattern stability is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of mobile device accessories, and particularly to a TPU mobile phone case for improving screen printing accuracy and a preparation method thereof. Background Art

[0002] With the continuous growth of personalized consumption demands, the screen printing process has become one of the main technologies for making colorful patterns on customized mobile phone cases. The demand for personalized mobile phone cases has promoted the innovation of printing technologies. However, due to the limitations of the mobile phone case materials themselves, technical bottlenecks are often encountered during the screen printing process, especially when the printed design includes patterns with complex details. Traditional thermoplastic polyurethane (TPU) materials have high elasticity, making the surface tension unstable, resulting in the printed patterns being prone to deformation. Especially as the complexity of the pattern details and text increases, the prior art cannot effectively ensure the sharpness of the pattern edges and the color saturation. This makes the produced mobile phone cases not only lack clarity in the visual effect but also affects the product consistency and aesthetics.

[0003] In the screen printing process of existing TPU mobile phone cases, problems such as blurred pattern edges and insufficient color saturation are common, especially when the design includes small text or complex lines. When conventional TPU materials bear printing ink, due to the unstable surface tension, it is difficult to ensure uniform ink adhesion, resulting in ink diffusion or penetration and forming blurred patterns. Even when using high-quality ink, the prior art still has difficulty overcoming problems such as insufficient pattern accuracy and poor color saturation. Especially in the detail part, this situation is particularly obvious, and the clarity of the text and the fineness of the lines often cannot meet the high-precision requirements of users for personalized patterns.

[0004] The prior art usually takes pretreatment measures, such as surface spraying of a hard coating or adjusting the ink formula. Surface spraying of a hard coating can increase the ink adhesion to a certain extent, but the thickness and hardness of the coating may cause the feel of the mobile phone case to deteriorate, losing the original elasticity and comfort of the TPU material. Secondly, an overly thick coating may cause the surface of the mobile phone case to lose its original softness and durability, and even affect the abrasion resistance of the mobile phone case. Problems such as coating peeling and fading may occur after long-term use. The adjustment of the ink formula also has certain limitations. Although formula optimization can improve the printing effect, it is difficult to take into account the physical properties of the raw materials, such as elasticity and scratch resistance, while improving the screen printing quality. During the production process, these measures not only increase the complexity of the process but also raise the production cost, making it difficult to meet the efficiency requirements of large-scale production. Summary of the Invention

[0005] In view of the deficiencies of the prior art, the present invention provides a TPU mobile phone case with improved screen printing accuracy and a preparation method thereof, which solves the problems of the existing preparation methods. The thickness and hardness of the coating may cause the feel of the mobile phone case to deteriorate, losing the original elasticity and comfort of the TPU material. An overly thick coating may cause the surface of the mobile phone case to lose its original softness and durability, and even affect the abrasion resistance of the mobile phone case. After long-term use, problems such as coating peeling and fading may occur.

[0006] To achieve the above objectives, the present invention is realized through the following technical solutions: The present invention provides a TPU mobile phone case with improved screen printing accuracy, which consists of the following components: 85% - 95% of modified TPU material. The modified TPU material improves the surface lipophilicity and surface energy by introducing terminal isocyanate. This modification effectively increases the compatibility between the material and the ink, making the screen printing pattern more accurate. The modified TPU material has excellent mechanical properties, with a tensile strength ≥ 20 MPa and an elongation at break ≥ 500%. This enables the material to be not only durable but also maintain deformation stability under complex processing conditions, thereby improving the basic stability of screen printing accuracy.

[0007] The terminal isocyanate reacts with the active hydrogen on the TPU molecular chain to introduce polar groups (such as hydroxyl or amine groups), thereby increasing the surface energy of the material. The increase in surface energy enables the ink to form a better wetting effect when contacting the material, reducing ink slippage or uneven distribution. In addition, intermolecular forces (such as hydrogen bonds or van der Waals forces) will be generated between the polar groups and the bonding molecules in the ink, further enhancing the adhesion of the ink. The high mechanical properties of the modified TPU provide a stable structural basis for screen printing processing, avoiding the influence of material deformation on the pattern under complex conditions.

[0008] 3% - 8% of functional additives consists of surfactants and nano modifiers.

[0009] The surfactant is selected as a fluoroalkyl coupling agent, which enhances the surface polarity of the material by forming a thin layer on the surface of the TPU. This effect improves the adhesion of the ink, making the screen printing effect clearer.

[0010] The fluoroalkyl coupling agent molecule has a special amphiphilic structure. Its hydrophobic chain segment binds to the TPU material, while the hydrophilic end groups are arranged on the material surface, forming a regular molecular layer. This molecular layer not only increases the surface energy of the material but also enables physical adsorption and chemical bonding between the ink and the surface molecules, significantly enhancing the adhesion performance of the ink. At the same time, the regular arrangement of the molecular layer also reduces the surface roughness, contributing to improving the clarity and uniformity of the screen printing pattern.

[0011] The nano modifier is amino-functionalized nano-silica with a particle size ranging from 50nm to 150nm, which can further improve the microstructure and surface properties of the material.

[0012] The amino-functionalized nano-silica is uniformly distributed on the surface of TPU through its small particle size (50nm - 150nm), filling the micro pores, thus flattening the surface structure. In addition, the amino groups and the polar molecules in the ink are further bonded by chemical bonds to enhance the adhesion. The filling effect of the nanoparticles also optimizes the surface tension distribution, avoiding uneven diffusion during the screen printing process and improving the accuracy of the pattern.

[0013] Pigment (1% - 3%).

[0014] Pigments with a particle size less than 1μm are used to ensure the uniform dispersion of the pigments in the material. The small particle size can avoid the formation of a rough surface due to particle aggregation, while not affecting the smoothness and pattern fineness after screen printing.

[0015] The smaller-sized pigment particles can significantly reduce the light scattering phenomenon on the material surface, making the screen-printed pattern more distinct and clear. In addition, the small size characteristics of the particles ensure the uniform distribution of the pigments in the TPU substrate, avoiding irregular interference on the screen-printed surface caused by particle accumulation. At the same time, the uniformly dispersed pigments can form a coating layer with high hiding power, which not only improves the color saturation but also enhances the edge sharpness and detail performance of the pattern.

[0016] Self-assembled coating material 2% - 3%.

[0017] The coating material is selected from polytetrafluoroethylene or polydimethylsiloxane, and its coating thickness is controlled between 0.02mm and 0.05mm. This coating material forms a uniform film on the surface of TPU through the dipping method, enhancing the wear resistance and screen printing stability of the material surface.

[0018] The fluorine groups or silicon groups in the coating material (such as PTFE or PDMS) molecules have extremely low surface energy, and this property significantly reduces the surface tension during ink adhesion, making the ink easier to spread evenly on the coating surface, thus reducing the interference factors in the screen-printed pattern and improving the screen printing accuracy.

[0019] The coating molecules have the ability of self-assembly and can form a regularly arranged thin layer on the material surface. This arrangement structure not only further reduces the surface roughness of the coating but also significantly enhances the mechanical stability and wear resistance of the coating, making the screen-printed pattern more durable.

[0020] The coating is uniformly coated by the dipping method, and its thickness is strictly controlled within the range of 0.02mm - 0.05mm. This thickness not only ensures the protection of the coating but also avoids the negative impacts that may be caused by too thick a coating on the touch and ink diffusion.

[0021] The present invention also provides a method for preparing a TPU mobile phone case with improved screen printing accuracy, which specifically includes the following steps: Step 1: Material mixing: The modified TPU, functional additives, and pigments are mixed according to the mass fraction ratio, and the mixing uniformity is ensured to be ≥ 95%.

[0022] Uniform mixing ensures the uniform distribution of the modifier and pigments in the material, thereby ensuring the improvement of the surface energy of the material and the full play of the optical properties of the pigments. In particular, the uniform distribution of the additives can avoid excessive or too low local polarity, reducing screen printing defects.

[0023] Step 2: High-temperature extrusion molding: The mixed material is extruded at a high temperature of 180°C to 220°C to form the main body of the TPU mobile phone case.

[0024] High-temperature extrusion melts and flows the material on the one hand, promoting the further uniform distribution of different components; on the other hand, by controlling the temperature range, it ensures that the modification effect and mechanical properties of the material are not damaged. In addition, the shearing effect during the extrusion process helps the molecular orientation arrangement of the additives on the material surface, laying a foundation for the subsequent screen printing effect.

[0025] Step 3: Coating with self-assembled coating: The extruded TPU mobile phone case is coated with self-assembled coating material by the dipping method, and the coating thickness is controlled between 0.02 mm and 0.05 mm.

[0026] The dipping method enables the coating material to be evenly distributed on the TPU surface through capillary action, forming a uniform thin film. The self-assembled characteristics of the coating (such as the automatic arrangement of fluorine groups in the polytetrafluoroethylene molecular chain) ensure the functionality of the coating. The coating not only provides wear resistance and surface smoothness, but also further improves the adhesion performance of the screen printing ink by adjusting the surface energy.

[0027] Step 4: Cooling and curing: The coated TPU mobile phone case is cooled and cured at 30°C to 40°C for 30 to 45 minutes.

[0028] The temperature control during the cooling process ensures the orderly arrangement and cross-linking curing of the coating material molecules, avoiding coating defects caused by rapid cooling. In addition, slow cooling can enable the full combination between the nanoparticles and the coating, improving the surface performance of the material.

[0029] The present invention provides a method for preparing a TPU mobile phone case with improved screen printing accuracy. It has the following beneficial effects: 1. By adopting the combination of modified TPU material and functional additives, the present invention achieves the effect of significantly improving the screen printing accuracy and pattern stability. Compared with the existing solutions that use ordinary TPU and traditional coatings, the latter often show blurring in the performance of pattern details, especially when printing small texts and complex lines. By adjusting the surface lipophilicity of TPU and using nano-silica and fluoroalkyl coupling agents, the present invention enhances the adhesion of the ink and the clarity of the pattern, solving the problems of pattern distortion and insufficient fineness in the existing solutions.

[0030] 2. By modifying the TPU material with terminal isocyanate, the present invention maintains its original resilience and scratch resistance while improving the screen printing quality. Different from the existing technology that sacrifices the physical properties of the material to improve the pattern quality, the present invention avoids this compromise. The modified TPU not only improves the screen printing effect but also enhances the durability and touch of the mobile phone case, making it more advantageous during long-term use.

[0031] 3. By optimizing the production process and adopting the methods of high-temperature extrusion molding and micro-layer coating, the present invention simplifies the traditional complex surface treatment process, achieving the technical effects of improving production efficiency and reducing costs. Compared with the existing technology with complex processes that require multiple pretreatment and surface spraying processes, the present invention omits the cumbersome spraying and coating hardening steps, reduces material waste and production time, greatly improves production efficiency, and reduces the overall manufacturing cost.

[0032] 4. By using a self-assembled coating of polytetrafluoroethylene (PTFE) or polydimethylsiloxane (PDMS), the present invention significantly improves the abrasion resistance and durability of the pattern. Compared with the problems in the existing technology that using too thick coatings may cause pattern fading and coating peeling, the present invention avoids such problems through a thin coating design, while enhancing the pattern stability, ensuring that even after long-term use, the pattern on the mobile phone case remains bright and clear, avoiding the troubles of premature wear and fading. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic diagram of the method flow of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0034] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the drawings of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0035] Please refer to the attached Figure 1, an embodiment of the present invention provides a method for preparing a TPU mobile phone case with improved screen printing accuracy, including the following steps: S1. Mix the modified TPU material, functional additives, and pigments by mass fraction. The mass fractions of each component are: 85% - 95% of the modified TPU material; 3% - 8% of the functional additives; 1% - 3% of the pigments.

[0036] S2. Extrude the mixed material at high temperature. The extrusion temperature is 180°C - 220°C to obtain the main body of the TPU mobile phone case.

[0037] S3. Coating the surface of the TPU mobile phone case with a self-assembled coating material. The coating thickness is controlled between 0.02 mm and 0.05 mm and is coated by the dipping method.

[0038] S4. Cool and cure the TPU mobile phone case coated with the self-assembled coating. The cooling temperature is controlled between 30°C and 50°C, and the curing time is 30 - 60 minutes.

[0039] Example 1: Step 1: Raw material mixing Take 85% modified TPU, 5% functional additives (including fluoroalkyl coupling agent and amino-functionalized nano-silica), 2% pigments (particle diameter less than 1 μm), and 8% other components (such as surfactants or other auxiliary components), and mix them evenly in proportion to ensure the uniform distribution of additives and pigments.

[0040] Step 2: High-temperature extrusion molding Put the mixed raw materials into the extruder, set the extrusion temperature at 190°C, ensure that the materials are completely melted, and avoid decomposition of components caused by overheating. After extrusion molding, obtain the main body of the TPU mobile phone case with a predetermined shape.

[0041] Step 3: Cooling and curing Naturally cool the molded mobile phone case at a temperature controlled at 30°C for 30 minutes to ensure the stable structure of the mobile phone case.

[0042] Step 4: Coating the surface micro-layer Dissolve the polytetrafluoroethylene (PTFE) coating material in an appropriate solvent, and coat it on the surface of the TPU mobile phone case by the dipping method. The coating thickness is maintained at 0.03 mm. After the coating is completed, dry it at room temperature for 30 minutes.

[0043] Example 2: Step 1: Raw material preparation Mix all raw materials evenly according to the ratio of 90% modified TPU, 3% functional additives (select silane coupling agent and hydrophobized nano-silica), 2% pigment, and 5% other components (such as surfactants or other auxiliary components) to ensure full fusion between materials.

[0044] Step Two: High-temperature extrusion molding Feed the mixed raw materials into the extruder, set the extrusion temperature at 210 °C to ensure the smooth melting of the modified TPU material and avoid the decline in ink quality caused by too high temperature. During the molding process, ensure uniform mixing to obtain a qualified TPU shell.

[0045] Step Three: Surface micro-layer treatment Evenly coat a polyamide-based coating with a thickness of 0.05 mm on the surface of the TPU shell. After the coating dries, the surface of the coating is flat, ensuring better adhesion of the screen printing ink and significantly improving the screen printing effect.

[0046] Step Four: Cooling and curing After completing the coating, put the product into the cooling device, set the cooling temperature at 40 °C, and control the curing time within 45 minutes to ensure the tight combination of the coating and the TPU substrate and high stability.

[0047] Example 3: Step One: Batching and mixing Use 85% modified TPU, 5% functional additives (including fluoroalkyl coupling agent and amino-functionalized nano-silica), 3% pigment (particle diameter less than 0.8 μm), and 2% other components (such as surfactants or other auxiliary components). Mix all materials evenly to ensure that each part can effectively play its role and achieve the best effect.

[0048] Step Two: Molding and extrusion Feed the pre-mixed materials into the extruder, set the extrusion temperature at 200 °C, and after the materials flow evenly, form the main body of the mobile phone case through the mold to ensure the smooth surface and precise shape of the shell.

[0049] Step Three: Surface coating and micro-layer formation Use polydimethylsiloxane (PDMS) as the coating material and control the coating thickness at 0.02 mm. After applying the coating, conduct low-temperature curing treatment to ensure the uniformity and stability of the coating, and increase the ink adhesion and pattern stability.

[0050] Step Four: Cooling and curing Cool the mobile phone case with the micro-layer coated, control the cooling temperature at 35 °C, and the curing time is 40 minutes to ensure that the physical properties of the mobile phone case are not affected and the pattern persistence is improved.

[0051] Comparative Example 1: Traditional TPU Comparison content: Modified TPU: Replace the modified TPU material with traditional TPU, and the rest of the content (functional additives, pigments, coatings, preparation process) is the same as that in Example 1.

[0052] Functional additives: Mix the raw materials evenly according to the proportion in Example 1 to ensure the uniform distribution of pigments and additives and avoid local unevenness.

[0053] Difference analysis: Since traditional TPU is not used, the surface energy of the traditional TPU material is relatively low and it cannot fully interact with the additive and ink molecules, even if the raw materials and additives are evenly distributed.

[0054] Preparation process: Use traditional TPU (unmodified) as the substrate, mix according to the ratio of 85% traditional TPU, 5% functional additives (including fluoroalkyl coupling agent and amino-functionalized nano-silica), 2% pigment (particle size about 1μm), and 8% other auxiliary components. After ensuring the uniform distribution of components, extrude the mixture at a high temperature of 190°C to form a preliminary mobile phone case body. Subsequently, naturally cool the mobile phone case body, control the cooling temperature at 30°C for 30 minutes to ensure the stable shape of the material. Spray a hard coating (such as polyurethane coating) on the surface of the cooled mobile phone case, control the coating thickness at 0.03mm, and then dry and cure at room temperature for 30 minutes to obtain the final product.

[0055] Comparative Example 2: No coating treatment Comparison content: Coating: No additional coating treatment, directly carry out the screen printing preparation process. The rest of the content (functional additives, pigments, preparation process) is the same as that in Example 2.

[0056] Preparation process: Use modified TPU (90%) as the substrate, add 3% functional additives (including silane coupling agent and hydrophobized nano-silica), 2% pigment (particle size less than 1μm), and 5% other auxiliary components (such as surfactant). After mixing all the raw materials evenly, form a TPU mobile phone case body through a high-temperature extrusion process (extrusion temperature is 210°C). The formed mobile phone case is cooled at 40°C for 45 minutes to ensure the structural stability. Different from Example 2, this comparative example does not perform any surface coating treatment and directly uses the cooled mobile phone case for screen printing. Due to the lack of coating protection and optimization, the surface performance is poor, and the ink adhesion and screen printing accuracy are significantly lower than those in Example 2.

[0057] Comparative Example 3: Excessive coating Comparison content: Coating: Using an excessive amount of coating (thickness about 0.1 mm) may lead to a decrease in pattern clarity and affect the feel at the same time. The remaining content (functional additives, pigments, preparation process) is the same as in Example 3.

[0058] Preparation process: Use modified TPU (85%) as the base material, add 5% functional additives (including fluoroalkyl coupling agent and amino-functionalized nano-silica), 3% pigments (particle size less than 0.8 μm), and 2% other auxiliary components (such as surfactants or other additives). After mixing all the raw materials evenly, feed them into an extruder for molding. The extrusion temperature is set at 200 °C to ensure that the raw materials are fully melted and evenly distributed. After molding, apply a 0.02 mm thick polydimethylsiloxane (PDMS) coating on the surface of the mobile phone case. After coating, the mobile phone case is cooled and cured at 35 °C for 40 minutes. Due to the excessive coating thickness, it is easy to cause ink diffusion during direct screen printing, resulting in poor pattern clarity and adhesion, and at the same time, the touch is hard and affects the overall durability of the product.

[0059] Experiment 1: Screen printing accuracy test experiment Experimental steps: Step 1: Prepare samples Select TPU mobile phone case samples from Example 1 and Comparative Example 1 respectively, ensuring that each group of samples is basically the same in shape and surface treatment.

[0060] Step 2: Screen printing pattern design Select a complex design pattern, including small text and complex lines, to test the screen printing accuracy. The pattern contains fine lines and text with a width of 0.2 mm.

[0061] Step 3: Screen printing operation Use an automated screen printing machine and set the unified screen printing parameters: pressure is 10 N, printing speed is 1.5 m / s, ink temperature is 25 °C, and humidity is maintained at 50%. Each sample is printed three times to ensure the reliability of the results.

[0062] Step 4: Check the screen printing effect After completing the screen printing, take pictures of the patterns of each group of samples using a high-resolution microscope. Record indicators such as the edge clarity, detail restoration, and color saturation of the patterns, and pay particular attention to the presentation of fine lines and small text.

[0063] Step 5: Evaluation and comparison Analyze the images through image processing software, calculate the edge clarity of the pattern (in pixels), and conduct a detail restoration evaluation. Finally, conduct a comprehensive evaluation based on criteria such as pattern distortion degree, detail clarity, and color consistency.

[0064] Experimental data: Table 1: Comparison of the results of the screen printing accuracy experiment Summary: Example 1 demonstrated higher screen printing accuracy and pattern clarity. The clarity of the thin lines and fonts in Example 1 reached 98 pixels and 95 pixels respectively, far higher than 85 pixels and 82 pixels of the control group. At the same time, the color saturation was also significantly better than that of the control group, reflecting the important role of the coating and functional additives in pattern restoration. This effect is closely related to the mechanism of the present invention. The improvement of surface lipophilicity and the introduction of functional additives effectively improved the adhesion of the ink, enabling the ink to be evenly distributed and firmly adhered, thus avoiding pattern distortion and blurring.

[0065] In addition, the self-assembly characteristics of the coating and the application of nanomaterials also played a key role in the clear restoration of pattern details. By using modified TPU and special coatings, the present invention effectively enhanced the surface microstructure of the TPU mobile phone case, enabling it to better adapt to the ink flow during the screen printing process and avoiding the common ink diffusion problem in traditional methods. The details were excellently presented, and the small characters and thin lines were clearly visible in Example 1, maintaining high clarity and saturation.

[0066] Generally speaking, the present invention significantly improved the pattern accuracy and screen printing effect compared with the traditional TPU solution, demonstrating the innovation and superiority of the present invention. Due to the efficient ratio of functional additives and the optimization of the coating microstructure, the pattern details were fully presented, and the pattern distortion and blurring phenomena were almost eliminated, bringing a breakthrough improvement to the screen printing technology. This not only improved the production efficiency but also enhanced the visual and tactile experience of consumers when using the mobile phone case.

[0067] Experiment 2: Ink Adhesion and Abrasion Resistance Test Experiment Experimental steps: Step 1: Prepare samples: Select the samples in Example 2 and Comparative Example 2 to ensure that the shapes and surface treatments of the two groups of samples are the same. Example 2 uses modified TPU material, silane coupling agent and nano-silica, and the coating thickness is 0.05 mm; the control group has no coating treatment, and the rest (functional additives, pigments, preparation process) is the same as that of Example 2.

[0068] Step 2: Ink adhesion test: Equipment: Coating adhesion tester (such as German tester), and the test is carried out according to the ISO2409 standard. Steps: Perform the same screen printing on the surfaces of the two groups of samples using the same batch of ink.

[0069] Use a standard hardness cutter for scratch testing, with the scratch frequency being 20 times and the pressure set at 10 N each time.

[0070] Observe the ink peeling situation and record the percentage of the ink shedding area.

[0071] Step 3: Abrasion resistance test: Equipment: Taber abrasion tester, conduct abrasion test according to ASTM D4060 standard. Steps: Take 10 samples each from Example 2 and the control group and put them into the abrasion tester.

[0072] Set the grinding wheel load at 500 g, the rotation speed at 60 revolutions per minute, and the test abrasion times at 1000 times.

[0073] After the test, use a microscope to observe the surface damage and record the color difference and the degree of surface damage after abrasion Experimental data: Table 2: Test results of ink adhesion and abrasion resistance Summary: Example 2 demonstrates significant advantages in ink adhesion and abrasion resistance. First, from the test results of ink adhesion, the ink peeling area of Example 2 is significantly lower than that of the control group, indicating that the use of modified TPU, functional additives, and coatings enhances the binding force between the ink and the surface. Compared with the samples without additional coating treatment in the control group, Example 2 shows more uniform and stable ink adhesion, which is closely related to the mechanism of using modified TPU and functional additives in this invention. By enhancing the lipophilicity and stability of the material surface, the ink can adhere firmly, reducing the ink peeling phenomenon.

[0074] In addition, in the abrasion resistance test, Example 2 shows lower wear depth and color difference changes, indicating that this solution can maintain better pattern stability and surface quality during long-term use. Compared with the control group, the surface damage of Example 2 is significantly less after the abrasion test, and the pattern fading is lighter, which reflects the significant improvement in surface hardness and scratch resistance provided by the self-assembled coating and nano-silica composite system used in this invention. The microstructure of the coating not only effectively protects the surface from scratch damage but also provides strong support for the durability of the pattern.

[0075] Generally speaking, this experiment verifies the effectiveness of the solution of this invention. In terms of improving ink adhesion, enhancing abrasion resistance, and increasing pattern durability, the solution without additional coating treatment provides significant technical improvements. These results are closely related to the mechanism of this invention. The combination of modified TPU material and functional additives not only enhances the lipophilicity of the surface but also improves the stability of the coating, enabling the ink to adhere more firmly to the surface and ensuring that the pattern maintains high quality during long-term use.

[0076] Experiment 3: Abrasion Resistance and Pattern Durability Test Experimental Procedure: Step 1: Sample Preparation Select Example 3 (modified TPU, fluoroalkyl coupling agent, nano-silica, 0.02 mm coating) and Comparative Example 3 with an excessive coating (thickness of about 0.1 mm). The rest of the content (functional additives, pigments, preparation process) is the same as that of Example 3 to ensure the same surface treatment method and the same size of the samples.

[0077] Step 2: Abrasion Resistance Test Use a Taber abrasion tester (compliant with ASTM D4060 standard) to conduct the abrasion test.

[0078] Set the load of the grinding head to 500 g and the speed of the grinding wheel to 60 revolutions per minute.

[0079] Conduct 1000 abrasion tests to simulate the friction conditions in daily use.

[0080] During the test, record the surface changes after abrasion, and observe the fading, abrasion degree of the pattern, and surface damage.

[0081] Step 3: Pattern Damage Assessment After the test, use a microscope to photograph the surface of the sample and observe the changes in the pattern, especially the abrasion of the detailed parts of the pattern.

[0082] Record the fading of the pattern, the degree of edge blurring, and the degree of pattern damage.

[0083] Use image analysis software to evaluate the retention of pattern details and record the clarity and color difference of the pattern.

[0084] Step 4: Comparative Analysis Compare the results of Example 3 and Comparative Example 3, especially in terms of pattern durability, surface damage caused by abrasion, color difference, etc., and analyze the performance differences in abrasion resistance between the two groups of samples. Experimental Data: Table 3: Comparative Results of Abrasion Resistance and Pattern Durability Test Summary: From the experimental data, Example 3 shows significantly better performance in terms of abrasion resistance and pattern durability than the control group. The pattern damage, color change, and pattern detail loss in Example 3 are all low, and the wear depth is also much lower than that of the control group. This difference stems from the combined use of modified TPU and functional additives in the present invention. In particular, the compounding of fluoroalkyl coupling agent and nano-silica enhances the surface lipophilicity and abrasion resistance of TPU. The molecular structure of the modified TPU enhances its scratch resistance, while nano-silica effectively improves the surface structure of the coating, enhances the adhesion and stability of the coating, and thus improves the pattern durability.

[0085] This experiment also verified the influence of coating thickness on abrasion resistance and pattern retention. The thin coating (0.02 mm) used in Example 3 can more effectively improve the ability to retain pattern details than the thick coating (0.1 mm) of the control group, while reducing the hand feeling problem caused by too thick a coating. The uniformity and micro-layer self-assembly structure of the coating improve the adhesion of the ink, avoiding pattern fading or peeling off due to excessive friction of the coating.

[0086] Through this experiment, it is proved that the technical solution of the present invention has significant effects in improving the durability of mobile phone cases, enhancing pattern clarity and durability. Compared with the traditional technology, Example 3 has achieved innovative breakthroughs in many aspects. These advantages will make the present invention have significant market competitiveness in terms of personalized customization, visual effects in long-term use, and user experience.

[0087] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A TPU mobile phone case for improving screen printing accuracy, characterized in that, It consists of the following components: 85% - 95% of modified TPU material; 3% - 8% of functional additives; 1% - 3% of pigments; 2% - 3% of self - assembled coating material.

2. The TPU mobile phone case for improving screen printing accuracy according to claim 1, wherein The modified TPU material is a thermoplastic polyurethane containing terminal isocyanate groups. Through modification, the lipophilicity and surface energy of the TPU surface are improved.

3. The TPU mobile phone case for improving screen printing accuracy according to claim 1, wherein The functional additives include surfactants and nano - modifiers. The surfactant is a fluoroalkyl coupling agent.

4. According to claim 3, a TPU mobile phone case for improving screen printing accuracy, characterized in that The nano - modifier is amino - functionalized nano - silica. The nano - modifier accounts for 1% - 2% of the raw materials of the TPU mobile phone case by weight percentage.

5. A TPU mobile phone case for improving screen printing accuracy according to claim 1, characterized in that, The particle size of the amino - functionalized nano - silica is 50nm - 150nm.

6. According to claim 1, a TPU mobile phone case for improving screen printing accuracy, characterized in that The coating material is polytetrafluoroethylene, polydimethylsiloxane or their blend. The mass fraction of the coating material is 2% - 3%.

7. A method for preparing a TPU mobile phone case with improved screen printing accuracy, which is applied to the TPU mobile phone case with improved screen printing accuracy described in any one of claims 1-6, characterized in that, It includes the following steps: Mix the modified TPU material, functional additives and pigments according to mass fractions; Extrude the mixed materials at a high temperature. The extrusion temperature is 180°C - 220°C to obtain the main body of the TPU mobile phone case; Coat the self - assembled coating material on the surface of the TPU mobile phone case; Cool and cure the TPU mobile phone case coated with the self - assembled coating. The cooling temperature is controlled at 30°C - 50°C, and the curing time is 30 - 60 minutes.

8. A method for preparing a TPU mobile phone case for improving screen printing accuracy according to claim 7, characterized in that, During the high - temperature extrusion molding process, the mixing uniformity of the TPU material is controlled above 95%.

9. A method for preparing a TPU mobile phone case for improving screen printing accuracy according to claim 7, characterized in that, The coating step of the self - assembled coating is carried out by dipping method on the surface of the main body of the TPU mobile phone case after extrusion molding. The coating thickness is uniformly controlled between 0.02mm - 0.05mm.

10. A method for preparing a TPU mobile phone case for improving screen printing accuracy according to claim 7, characterized in that, During the cooling and curing process, the cooling temperature is 30°C - 40°C, and the curing time is 30 - 45 minutes.

Citation Information

Patent Citations

  • High-strength light-weight nano cell phone housing

    CN111013992A

  • Layer-by-layer self-assembled nanofiltration membrane as well as preparation method and application thereof

    CN119565398A

  • stretchable and compressible 3D coating emulsion as thermal transfer

    DE202016006953U1